2022
DOI: 10.48550/arxiv.2202.03272
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Classical shadows with Pauli-invariant unitary ensembles

Abstract: The classical shadow estimation protocol is a noise-resilient and sample-efficient quantum algorithm for learning the properties of quantum systems. Its performance depends on the choice of a unitary ensemble, which must be chosen by a user in advance. What is the weakest assumption that can be made on the chosen unitary ensemble that would still yield meaningful and interesting results? To address this question, we consider the class of Pauli-invariant unitary ensembles, i.e. unitary ensembles that are invari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…( 3) is the inverse of the channel C E . It has been observed that for certain classes of measurements, the inverse channel C −1 E is particularly simple [7,27]. We are to show that behind this simplicity is the symmetry of the generalised measurement, which can be generalised to a much broader class of measurements.…”
Section: Symmetric Generalised Measurements and The Computation Of Th...mentioning
confidence: 88%
“…( 3) is the inverse of the channel C E . It has been observed that for certain classes of measurements, the inverse channel C −1 E is particularly simple [7,27]. We are to show that behind this simplicity is the symmetry of the generalised measurement, which can be generalised to a much broader class of measurements.…”
Section: Symmetric Generalised Measurements and The Computation Of Th...mentioning
confidence: 88%
“…In our analysis, we assumed the Clifford circuit in the classical shadow part is noise-free. If there are noise in the Clifford circuit part, it can be mitigated if the noise is independent of the Clifford gates, as in [27][28][29], where similar idea was used for randomized benchmarking [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent to version 1 [53] of our manuscript, several new extensions and applications of classical shadows have been developed [48,49,. Amongst these are extensions of the classical shadows framework to quantum channels [71,72] and to more general ensembles, like locally scrambled unitary ensembles [69] and Pauli-invariant unitary ensembles [77]. Additional applications of classical shadows include avoiding barren plateaus in variational quantum algorithms [76], quantifying information scrambling [78], and estimating gate set properties [73].…”
Section: Classical Shadowsmentioning
confidence: 99%